2014
DOI: 10.2147/lra.s62160
|View full text |Cite
|
Sign up to set email alerts
|

Preventive analgesia for postoperative pain control: a broader concept

Abstract: Pain from surgical procedures occurs as a consequence of tissue trauma and may result in physical, cognitive, and emotional discomfort. Almost a century ago, researchers first described a possible relationship between intraoperative tissue damage and an intensification of acute pain and long-term postoperative pain, now referred to as central sensitization. Nociceptor activation is mediated by chemicals that are released in response to cellular or tissue damage. Pre-emptive analgesia is an important concept in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 49 publications
(52 reference statements)
0
65
0
1
Order By: Relevance
“…Pain is also one of the primary concerns of the surgeon because of its close ties with clinical outcome and acute postoperative patient well-being. Studies have indicated such negative clinical outcomes to include decreases in vital capacity and alveolar ventilation, pneumonia, tachycardia, hypertension, myocardial ischemia, myocardial infarction, transition to chronic pain, poor wound healing, and insomnia 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Pain is also one of the primary concerns of the surgeon because of its close ties with clinical outcome and acute postoperative patient well-being. Studies have indicated such negative clinical outcomes to include decreases in vital capacity and alveolar ventilation, pneumonia, tachycardia, hypertension, myocardial ischemia, myocardial infarction, transition to chronic pain, poor wound healing, and insomnia 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Nerve blockade could reduce the risk of persistent postoperative opioid use through one of two mechanisms. The first, a theory known as preventative analgesia, 7375 suggests that nerve blockade can prevent the transition from acute to chronic pain by directly blocking transmission of pain impulses during the perioperative period and thereby preventing central sensitization and chronic neuropathic pain. Second, nerve blocks are a well-established modality for treating acute post-operative pain, which when severe, is predictive of the development of chronic pain.…”
Section: Strategies To Promote Opioid Cessation After Surgerymentioning
confidence: 99%
“…2 A combination of preoperative and multimodal analgesia can significantly decrease acute pain. 3 Recent research in spinal, obstetric, and cardiac surgery has shown the unique potential of intravenous methadone, which, in addition to its long halflife, has mu opiate as well as N-methyl-D-aspartate receptor (NMDA) effects on pain. [4][5][6][7][8] No published studies to date have used methadone delivered via the oral route.…”
Section: Introductionmentioning
confidence: 99%